Analisis Putusan Bebas Dalam Perbuatan Pidana Pemalsuan Buku Pemilikan Kendaraan Bermotor (Studi Putusan Pengadilan Negeri Kendal Nomor 21/Pid.B/2022/PN Kdl) - Djiwandana, Alif Djangkung; Rosando, Abraham Ferry (CV. Era Digital Nusantara, 2025)
The falsification of Motor Vehicle Ownership Documents (BPKB) is a prevalent type of criminal offense due to its high economic value, making it commonly used as collateral for credit. This research is based on the decision of the Kendal District Court Number 21/Pid.B/2022/PN Kdl, which acquitted the defendant in a BPKB falsification case, despite the public prosecutor charging the defendant under Article 263 of the Indonesian Criminal Code (KUHP). This study aims to analyze: (1) the legal position of the defendat in the criminal act of BPKB falsification, and (2) the legal considerations of the judge in acquitting the defendant. This research uses a normative juridical method with a statutory approach and case approach. The data sources consist of primary legal materials such as the Indonesian Criminal Code and court decisions, as well as secondary legal materials such as legal literature and expert opinioons. The results of this research show that the defendant was not legally and concincingly proven to have forged or falsified the BPKB as referred to in Article 263 of the Criminal Code. The defendat merely acted as a supplier of original BPKB documents without the Vehicle Registration Certificate (STNK) and the vejicle itself, without direct involvement in falsifying the content of the documents. The judge considered that the elements of the offense were not fulfilled and applied the legal principle of in dubio pro reo, thus acquitting the defendant.